Comparison of the anthropometric measurements and health risks in people with normal weight according to the body mass index-for-age charts (Faculty of Medicine Universitas Indonesia, 2009)
Aim Body mass index (BMI) at 5th-84th percentiles according to the BMI-for-age charts from Center for Diseases Control and Prevention (CDC) is considered as normal BMI for children and adolescents. However, Guo et al found that BMI at 75th-84th percentiles already had a possibility to be adult overweight and obese. This study aimed to determine anthropometric measurements, laboratory findings, and health risk differences to find an ideal BMI group according to the BMI charts. Methods Normal BMI according to adult classification from the World Health Organization (BMI at 18.5-24.9) is used as a reference group. Results & Conclusion Our study showed BMI value at 50th-74th percentiles in boys and at 75th-84th percentiles in girls had higher anthropometric measurements and laboratory findings than the reference group. However, the health risks of those BMI percentiles did not significant different compared with the reference group. (Med J Indones 2009; 18: 41-7) Keywords: normoweight, adolescent, BMI-for-age charts, anthropometric measurements, health risks